Effects of different urban vegetation cover and green space types on soil greenhouse gas emissions and carbon sequestration - Zhang, Ruisha; Cheng, Xuekun; Chen, Wu; Lu, Feng; Liu, Shuhan; Shi, Haitao; Ni, Zelong; Chen, Yangen; Li, Dabiao; Zhou, Yufeng; Shi, Yongjun (Frontiers in Environmental Science, 2025)
The development of urbanization has led to the creation of various types of green spaces, which have a direct influence on vegetation types and soil management, This, in turn, results in differences in soil carbon sequestration capacities. However, the factors affecting soil carbon sequestration in different vegetation types within urban green spaces remain largely unexplored. To address this gap, the study focused on the soil of urban green space. A one-year field observation was conducted, utilizing local management archives and historical data, to evaluate variations in soil greenhouse gas (GHG) emission and soil organic carbon sequestration across grassland (GL), shrubs (SH), and forests stands (FS) within three types of green spaces: park green space (P), residential green space (Ra), and street green space (s). The results indicated that: (1) In comparison to grassland (GL), the CO2 flux of shrubs (SH) and forests stands (FS) declined by 10.73% and 14.46%, respectively, while the N2O and CH4 fluxes remained insignificant. Additionally, the annual increase in soil organic carbon was lower by 8.92% and 10.80% in shrub and forests stand, respectively; (2) Variations in greenhouse gas fluxes were also observed among the three types of green spaces. In comparison to park green spaces, the CO2 flux of residential and street soils decreased by 2.11% and 3.25%, respectively, while the N2O flux dropped by 16.61% and 22.41%, respectively. The CH4 flux remained insignificant. The annual increase of SOC in residential and streets was notably lower than that in parks green spaces, by 9.59% and 15.20%, respectively, indicating significant differences. This suggests that soil carbon sequestration capacity is highly responsive to changes in vegetation coverage and green space types, with WSOC, NH4+-N, and pH identified as the primary factors influencing the greenhouse gas flux in the three soils. This study provides data and a theoretical basis for the strategic selection of urban soil management measures, particularly in the context of achieving carbon neutrality goals.